2022
DOI: 10.1002/admi.202200464
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Efficiency Enhancement of Perovskite Solar Cells Using Phenyltriethylammonium Iodide

Abstract: Controlling the perovskite film surface is key to improving both the stability and photovoltaic performance of perovskite solar cells. In particular, surface defects on the perovskite films, which are fundamental issues, must be passivated. This work presents a 2D organic material phenyltriethylammonium iodide (PTEAI) to passivate a 3D (FAPbI3)1−x(MAPbBr3)x perovskite film surface. PTEAI forms a well‐matched conformal layer on the perovskite film, protecting the film surface from moisture by preventing the esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…26 After DAI treatment, new absorption peaks appear at 3024 and 766 cm À1 , which correspond to the symmetric stretching of the methylene (CH 2 ) group and the N-H wag from the secondary amine in DAI, respectively. 27 These new peaks indicate the successful incorporation of DAI on top of the 3D perovskite.…”
Section: Paper Pccpmentioning
confidence: 97%
“…26 After DAI treatment, new absorption peaks appear at 3024 and 766 cm À1 , which correspond to the symmetric stretching of the methylene (CH 2 ) group and the N-H wag from the secondary amine in DAI, respectively. 27 These new peaks indicate the successful incorporation of DAI on top of the 3D perovskite.…”
Section: Paper Pccpmentioning
confidence: 97%
“…For stability, the devices based on PETAI maintained 92% of the original efficiency after aging for 500 h under continuous illumination in a high‐humidity atmosphere. [ 114 ] Jeong et al. compared the influence of alkyl chains of 2D cations of LDPHS on the photoelectric properties of PSCs (CHAI and CHAMI).…”
Section: Energy Level Tailoring and Passivationmentioning
confidence: 99%
“…For stability, the devices based on PETAI maintained 92% of the original efficiency after aging for 500 h under continuous illumination in a high-humidity atmosphere. [114] Jeong et al compared the influence of alkyl chains of 2D cations of LDPHS on the photoelectric properties of PSCs (CHAI and CHAMI). The TRPL measurements showed that the samples based on 2D organic cation without alkyl chain modification exhibited faster interfacial carrier injection due to the lower valence band of perovskite surface.…”
Section: Low-dimensional Perovskite Halide Saltmentioning
confidence: 99%
“…Interface engineering is an efficient and reliable strategy, which mainly through interface modification, adding buffer layers, dopant and so on to optimize interfacial contact and film morphology. [ 18–20 ] Appropriate interface engineering not only can achieve energy level alignment, but also passivate surface defects, which greatly improves the PCE of PSCs. [ 21,22 ] For instance, Xu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Interface engineering is an efficient and reliable strategy, which mainly through interface modification, adding buffer layers, dopant and so on to optimize interfacial contact and film morphology. [18][19][20] Appropriate interface engineering not only can achieve energy level alignment, but also passivate surface defects, which greatly improves the PCE of PSCs. [21,22] For instance, Xu et al introduced the (CsPbI 2 Br) 1−x (CsPbI 3 ) x layer as intercalation layer between CsPbI 2 Br film and hole transport layer (HTL) to minimize the energy loss, resulting in good crystalline quality and energy level alignment.…”
mentioning
confidence: 99%